2018
DOI: 10.1111/bjet.12657
|View full text |Cite
|
Sign up to set email alerts
|

The effects of m‐learning on motivation, achievement and well‐being: A Self‐Determination Theory approach

Abstract: From the lens of Self‐Determination Theory, this study investigated the effects of a mobile application tool for identifying species on biology students’ achievement and well‐being. It was hypothesized that the mobile application, compared to a textbook, would enhance feelings of competence and autonomy and, in turn, intrinsic motivation, positive affect and achievement, because the mobile application’s built‐in functions provide students with choice and volition, informational feedback, and optimal challenges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
57
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(69 citation statements)
references
References 30 publications
6
57
1
5
Order By: Relevance
“…As the Yeager et al, quote above makes clear, the backdrop for the studying behaviors exhibited by adolescents is complicated. Issues of autonomy, competence, and relatedness (i.e., self-determination theory) are natural directions to investigate to determine how to best support learners (Deci & Ryan, 2012;Jeno, Adachi, Grytnes, Vandvik, & Deci, 2019). This is particularly relevant in an era of hyper-connectivity where the erosion of time and space boundaries suggest that adolescents should always be available.…”
Section: Interventionmentioning
confidence: 99%
“…As the Yeager et al, quote above makes clear, the backdrop for the studying behaviors exhibited by adolescents is complicated. Issues of autonomy, competence, and relatedness (i.e., self-determination theory) are natural directions to investigate to determine how to best support learners (Deci & Ryan, 2012;Jeno, Adachi, Grytnes, Vandvik, & Deci, 2019). This is particularly relevant in an era of hyper-connectivity where the erosion of time and space boundaries suggest that adolescents should always be available.…”
Section: Interventionmentioning
confidence: 99%
“…M-learning can be implemented across different levels of education. However, it is highly relevant in the higher educational context, as the university students will already have their own mobile devices [22]. A thorough review of the literature suggests that there a few empirical studies that have explored the students' readiness to use the m-learning technologies; although there are a number of studies that have investigated the users' acceptance of other educational technologies, including; digital learning resources, WebCT or Moodle systems ( [10], [19]).…”
Section: Literature Review 21 the Conceptual Development And The Formentioning
confidence: 99%
“…However, there has been limited empirical research that identified the factors affecting the university students' adoption of m-learning technologies, albeit a few exceptions ( [19], [20], [21], [22].…”
Section: Introductionmentioning
confidence: 99%
“…The academic community is also aware of this transformation, investigating several different research topics in this area, like the effects of mobile learning in motivation and well being (Jeno et al 2019), how to evaluate the student satisfaction in e-learning applications (Violante and Vezzetti 2015) or how to assess the overall quality of Massive Open Online Courses (MOOCs) (Foley et al, 2019).…”
Section: Introductionmentioning
confidence: 99%